Stepwise enhancement on optoelectronic performances of polyselenophene via electropolymerization of mono-, bi-, and tri-selenophene. (20th April 2020) - Lu, Baoyang; Jian, Nannan; Qu, Kai; Hu, Faqi; Liu, Ximei; Xu, Jingkun; Zhao, Guoqun
Abstract: Although much progress have been made on polyselenophenes-based molecular systems, the poor optoelectronic performance of parent polyselenophene still hamper both the fundamental understanding and practical applications of such materials due to the monomer instability during the polymerization process and the lack of suitable monomeric precursors. In this work, we develop an effective method to improve the optoelectronic performances and stability of parent polyselenophene by stepwise increasing the initial monomeric chain length for electrochemical polymerization. We find that the chain length increment of the monomeric structures from selenophene to bi- and tri-selenophenes dramatically reduces the electropolymerization potential and thus enables the formation of high quality polyselenophene films with better conjugated structures and less structural defects. As-formed polyselenophene from tri-selenophene reveals lowered optical band gap (1.72 eV), better redox activity and stability, and significantly improved electrochromic nature of reversible and stable color changes between red and blue with high performance including superior optical contrast up to 75%, high coloration efficiency up to 450 cm 2  C −1, and very fast switching time (0.7 s for oxidation and 0.4 s for reduction). These advantageous properties of as-prepared polyselenophene films afford the successful fabrication of patterned flexible electrochromic devices, which exhibit reversible and stable color changes upon both doping-dedoping and mechanical bending. Graphical abstract: The chain length increment of the monomeric structures from selenophene to bi- and tri-selenophenes dramatically reduces their corresponding electrolysis potential and also structural defects of the resultant polyselenophene. Polyselenophene from bi- and tri-selenophene reveals superior optical contrast (60%), high coloration efficiency (224 cm 2  C −1 ), and significantly improved redox stability. Flexible electrochromic devices display reversible and stable color changes upon long term bending. Image 1 Highlights: Stepwise enhancement from the chain length increment of varying selenophenes on the properties of polyselenophene. Polyselenophene from bi- and tri-selenophene reveals superior electrochromic properties and redox stability. Flexible electrochromic devices display reversible and stable color changes upon long term bending.